Developing the Facebook-Problem Based Learning Model: A Way of Improving the Geographical Solving-Problem Skills at Senior High Schools - Sumanti, Sumanti; Effendi, Z. Mawardi; Ridwan, Ridwan; Festiyed, Festiyed (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
The primary purpose of this study was to develop a model of learning based on Facebook-assisted learning to improve the geographic problem-solving abilities of high school students. Research and Development was the type of research entailed. Instructional System Design entailed was Plomp consisting of (1) preliminary research (2) Prototype Phase (Prototyping phase); 3) Assessment stage. The product design stage investigates the validity and practicality with formative evaluations which include self-evaluation and one-to-one. The assessment stage uses summative evaluation which aims to assess the validity of the product in aspects of the organization, format, material and language. Practicality assesses the level of ease, the efficiency of time and benefits. As for effectiveness, it assesses student learning test results using the t-test. Exam questions are made in the form of essays and are assessed using an assessment rubric. Data is collected through discussions, observations, interviews, questionnaires and tests. The collected data were analyzed using descriptive and inferential statistics. The results showed that for the validity of the Model book and its support system (teacher's books and student books) met the valid criteria of> 3.20 while the ICC value of the model book was 0.987, the ICC of student books was 0.943 and ICC of the teacher's book 0.965. These figures indicate that the model and the supporting system according to the expert is appropriate. The practicality results obtained are very practical that is easy to use, understood, very helpful in the learning process, the use of adequate time, and fun for students to learn. Effectiveness test results enable students to solve Geography problems in High Schools. In conclusion, the Valid, practical and effective Facebook-assisted problem-based learning model can improve the geography problem-solving ability of high school students. , e-learning, facebook